Strategies for Improving Employee Performance at the Consumer Credit Processing Center Division of Bank BNI Pejompongan - SY, Supriyatin (SEAN Institute, 2023)
The goal of this study is to look at the elements that influence employee performance at the PT Bank BNI Pejompongan consumer credit processing center division. Work discipline, the work environment, salary, and work ability are examples of these factors. The current study is a descriptive and correlational study, and the statistical analysis method used was the coefficient of determination, which was completed with SPSS version 25.0. According to the findings, the variable